Compatibility of nickel and silver‐based brazing alloys with E85 fuel blends. Issue 2 (11th December 2013) - Dimatteo, A.; Lovicu, G. F.; Desanctis, M.; Valentini, R.; Santarelli, S.; Cognetta, F.
<x xml:space="preserve">Abstract</x> In this study, the corrosion behavior of AISI 304 fuel rail brazed joints in presence of ethanolic E85 fuel has been evaluated. The galvanic corrosion resulting from coupling steel and copper brazing alloys has been studied as it represents a potential risk for the functionality of the fuel rail and injectors. The corrosion can lead to nozzle clogging by the increase of level of solute metallic ions or rupture of the joint itself. Tests have been carried out both on specimens simulating the brazed joints and on real fuel rail component. Static immersion tests and static filling tests in standard gasoline, E85 and modified E85 fuels have been carried out. The latter have been prepared by adding aggressive reagent, such as acetic acid, sulfuric acid, and chlorides, to the E85 fuel. Tests have been carried out at room temperature and at 60 °C. Alternative brazing materials to copper alloys (nickel‐ and silver‐based alloys) have also been tested, with the aim of comparing their corrosive resistance. From results here obtained, the nickel‐based brazing alloys, which have been tested because of their intrinsic ability to passivate, have proved to be more resistant to corrosion than copper, but only during exposure to commercial E85 and at room temperature. Silver‐based brazing alloys have shown poor resistance to corrosion and the tendency of soluted Ag ions to precipitate in presence of chloride ions.